Desempenho térmico de pavilhões industriais: estudo de casos em Panambi/RS - Malheiros, Fabiane Van Ass (2005)
This work aims the analysis of two typologies of the most used industrial buildings in the region of the Municipality of Panambi-RS, one with Shed Cover and the other with Continuous Vent Cover. A survey on constructive characteristics was conducted, relating them to the thermal performance, of the buildings and to the thermal comfort conditions which were obtained from measurements of the ambient variables of air temperature, radiant medium temperature, relative humidity and air velocity for summer and winter periods. The human variables, metabolic rate of heat production and clothing used by the workers, were also analyzed. With the results obtained, the thermal performance was analyzed relating to the temperature outside the buildings, and an evaluation of the thermal comfort was conducted inside the working environments. Two alternatives were then presented to enhance the environments of these buildings mainly concerning to decrease the thermal transmittance and the absorption coefficient of evolving solar radiation of buildings and also improvements of thermal conditions of external air. The study offers important inputs and boundaries for future projects of industrial pavilions.